2010
DOI: 10.1111/j.1600-0609.2010.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus (EBV) genotypes among human immunodeficiency virus (HIV)‐related B‐cell Lymphomas and B‐cell post‐transplant lymphoproliferative disorders (B‐PTLD) – late‐onset lymphomas, especially in the HIV setting, are associated with type‐B‐EBV

Abstract: We investigated 26 B-cell post-transplant lymphoproliferative disorders (B-PTLD) and 15 human immunodeficiency virus-related aggressive B-cell lymphomas (HIV-BCL) from England that were associated with Epstein-Barr virus (EBV) for the polymorphic sequences of the EBV-encoded nuclear antigen 3C (EBNA3C) gene to distinguish the two different EBV strains. Type-A-EBV was identified in 92% of B-PTLDS and in 53% of HIV-BCL (P = 0.003). Among HIV-BCL, patients associated with type-B-EBV had been HIV positive for sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
3
12
1
Order By: Relevance
“…In patients with LPD, all subjects were infected with genotype A. This is consistent with other post-transplant LPD (or PTLD) studies in the UK and USA, which found genotype A in 89–92% of transplant recipients [29,44]. …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In patients with LPD, all subjects were infected with genotype A. This is consistent with other post-transplant LPD (or PTLD) studies in the UK and USA, which found genotype A in 89–92% of transplant recipients [29,44]. …”
Section: Discussionsupporting
confidence: 88%
“…Moreover, genotype A was isolated from all study groups and was not limited to a specific disease. Other studies have found a similar result, with genotype A detected in a range of EBV-related conditions, including IM, chronic active EBV infection, post-transplant lymphoproliferative disease (PTLD), AIDS, EBVAHS, autoimmune hepatitis, Hodgkin’s lymphoma and gastric carcinomas [14,29,30,31,32,33]. These findings are consistent with EBV genotypes being geographically restricted rather than disease-specific [34,35].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Patients with primary immune disorders are more likely to develop benign T-cell expansions of CD4-/CD8-α/β T cells than T-cell malignancies. HIV-positive patients may develop a spectrum of lymphoid proliferation including: reactive hyper plasia, AtLP, lesions resembling polymorphic B-cell post-transplant lymphoproliferative disorders and malignant lymphomas [29].…”
Section: Proposed Etiologies Of Atlpmentioning
confidence: 99%